Toll-like receptor 2 signaling pathway activation contributes to a highly efficient inflammatory response in Japanese encephalitis virus-infected mouse microglial cells by proteomics - Zhao, Guanyu; Gao, Yan; Zhang, Jiaqi; Zhang, He; Xie, Changzhan; Nan, Fulong; Feng, Sheng; Ha, Zhuo; Li, Chenghui; Zhu, Xiangyu; Li, Zhuoxin; Zhang, Ping; et al. (Frontiers in Microbiology, 2022)
Thousands of people die each year from Japanese encephalitis (JE) caused by the Japanese encephalitis virus (JEV), probably due to exacerbation of the inflammatory response that impairs the course of the disease. Microglia are mononuclear phagocytic cells located within the parenchyma of the central nervous system; these play a key role in the innate immune response against JEV infections. However, the involvement of toll-like receptor 2 (TLR2) in the inflammatory response during the early stages of JEV infection in BV2 cells remains. Here, we evaluated protein profiles and determined the role of TLR2 in the inflammatory response of JEV-infected BV2 cells. High-depth tandem mass tags labeling for quantitative proteomics was used to assess JEV infected-BV2 cells and compare immune response profiles at 6, 12, and 24 h post-infection (hpi). In total, 212 upregulated proteins were detected at 6 hpi, 754 at 12 h, and 191 at 24 h. According to GO and KEGG enrichment analysis, the upregulated proteins showed enrichment for proteins related to the immune response. Parallel reaction monitoring tests, western blotting, and qPCR results showed that the adaptor protein MyD88 was not activated. The expression levels of key proteins downstream of MyD88, such as IRAK1, IRAK4, and TRAF6 did not increase; however, the expression levels of PI3K-AKT did increase. By inhibiting key proteins (TLR2, PI3K, and AKT) we confirmed that JEV activated TLR2, thus resulting in a robust inflammatory response. Consequently, the TLR2-PI3K-AKT signaling axis was proven to play a critical in the early stages of the JEV infection-induced inflammatory response in microglia.